Synthesis and Characterisation of Silver–2-Phenylenediamine–Cyclodextrin Nanomaterials (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The spectral characteristics of 2-phenylenediamine (2PDA) in various solvents, and in the presence of α-cyclodextrin (α-CD) and β-cyclodextrin (β-CD) at pH~3, and pH ~7, were investigated using UV–visible, fluorescence, time-resolved fluorescence measurements, and PM3 computational methods. 2PDA showed a single broad emission band in all solvents, whereas dual emission observed in CD solutions indicates the presence of excimer in the 2PDA molecule. The fluorescence lifetimes of the inclusion complexes were greater than that of free 2PDA. In the 2PDA molecule, both the vertical and horizontal bond lengths between the both amino groups are smaller than the β-CD cavity size The Ag:2PDA:α-CD and Ag:2PDA:β-CD nanomaterials were synthesized and characterized by SEM, FTIR, and DSC techniques. In all pH conditions, 2PDA exhibited distinct absorption and emission shifts upon complexation with α-CD and β-CD. SEM–EDX data confirmed the presence of 5.5% silver in the nanomaterials.